Assessment of the Patient with Low-Risk Non-St Segment Elevated Myocardial Infarction Undergoing Invasive Coronary Angiogram Based on Up-Front Non-Invasive Imaging - Haque, Mostashirul; Singha, Chayan Kumar; Sarkar, Asish Kumar; Khaled, Md Fakhrul Islam; Osmany, Din E Mujahid Mohammad Faruque; Mahmud, Sohel; Ahmed, Choudhury Meshkat (University Heart Journal, 2025)
Background: Routine ICA to detect significant CAD is risky, costly, and likely unnecessary in cases of type- 2 MI or non-ischemic injury. This study evaluates noninvasive imaging as a safer, cost-effective alternative to guide ICA decisions. Methods: This descriptive cross-sectional study was conducted at the echo and Cath laboratory as well as CT imaging laboratory of BSMMU. Two groups were created from the noninvasive imaging procedures. Anatomic imaging: CT angiography, Physiologic imaging which is subdivided SPECT-MPI and DSE. Sensitivity, specificity and predictive values of these anatomic and physiologic imaging was calculated. When initial CTA or MPI or DSE suggested myocardial ischemia/infarction/obstructive CAD, follow-up ICA was recommended and calculated. Results: We have consecutively included 94 patients. In this study revealed that up-front CT detecting obstructive CAD of patient undergoing ICA sensitivity of 94%, specificity of 87%, PPV 89% and NPV 91%. Up-front SPECT MPI had a 92% sensitivity, 75% specificity, and 83% accuracy rate in identifying coronary artery disease in patients going through ICA. Up-front DSE detecting CAD of patient navigating ICA sensitivity of 84%, specificity of 81% and accuracy of 83%. Conclusion: In order to accurately diagnosis and management of CAD along with reducing unnecessary invasive procedure, this study found that patients with low-risk ACS had undergone a non-invasive imaging approach before navigate through coronary angiogram. University Heart Journal 2025; 21(1): 35-41